Integrative medicine and perinatal outcomes among women giving birth: A national population-based study in South Korea - Seongju Kim; Jiae Choi; Hye Won Lee; Sunju Park (Integrative Medicine Research)
Background: The aim of this study was to examine the effects of integrative medicine (IM) on perinatal outcomes and health care utilization in women who gave birth in Korea. Methods: This study used National Health Insurance Sharing Service (NHISS) claims data and established a retrospective cohort of all women who gave birth in Korea from January to December 2021. The women were categorized into IM and conventional medicine (CM) groups according to the nature of their health institution visits before delivery. To assess the risk of adverse perinatal outcomes between the two groups, a logistic regression model was used to estimate the odds ratio (OR) and the corresponding 95 % confidence interval (CI). Results: A total of 171,136 women were divided into the IM (n = 91,902) and CM (n = 79,234) groups. Among the 9,608,545 claims analyzed, respiratory system disease was the most common primary diagnosis, followed by genitourinary system diseases. In the IM group, 19,153 claims were associated with infertility diagnosis codes, with the most frequent primary diagnoses being female infertility associated with anovulation and female infertility of other origins. Compared with the CM group, the IM group had significantly greater rates of assisted reproductive technology (ART) use (aOR, 1.25 [95 % CI, 1.21, 1.29]; P < 0.0001) and cesarean delivery (aOR, 1.08 [95 % CI, 1.06, 1.11]; P < 0.0001). Conclusion: The study findings support that dual health care system use is not associated with the health outcomes of women who gave birth. The findings are expected to be valuable for establishing national health and medical policies or promoting health care utilization for women who give birth in South Korea.